Serum Biochemical Changes in Alloxan-induced Diabetic Rats and Ameliorative Effects of Moringa oleifera and Morinda lucida Leaf Extracts - Amadi Anthonia Nnenna Chuks; Chinedu-Ndukwe Peace Amarachi; Ijioma Solomon Nnah; Robert Ikechukwu Uroko; Madubike Kelechi Gideon (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
This study evaluated the antidiabetic properties and biochemical changes in alloxan-induced diabetic rats treated with Moringa oleifera and Morinda lucida leaf extracts. The acute toxicity values of the extracts were determined before evaluating their antidiabetic effects in 7 groups of 4 rats each. Rats in groups 1-6 were made diabetic via a single injection of alloxan monohydrate (160 mg/kg i.p). Animals whose blood glucose levels rose to 200 mg/dl and above were considered diabetic and used for the study, but group 7 was the normal control. Groups 1 and 2 received 500 and 250 mg/kg of M. oleifera extract, respectively, while groups 3 and 4 received 500 and 250 mg/kg of M. lucida extract, respectively. Group 5 received 3 mg/kg of the standard drug (Daonil), while groups 6 and 7 were the diabetic and normal control groups, respectively. Treatment lasted for 21 days and was administered orally. The phytochemical screening results showed that each of the extracts was rich in phytochemical agents. Higher amounts of flavonoids and terpenoids were found in M. oleifera, while M. lucida had higher phenols and saponins. LD50 value obtained for each extract was above 5000 mg/kg. Results of the antidiabetic study indicated that the extracts significantly brought down glucose levels in the test rats (p<0.05) when compared with the diabetic control. Treatment also restored elevated lipids values, liver function, and renal function parameters in the diabetic rats. The decreased glutathione, catalase, and superoxide dismutase activities and increased lipid peroxidations resulting from diabetes mellitus induction were also significantly corrected following extracts administration when compared with the diabetic control (p<0.05). Our findings show that Moringa oleifera and Morinda lucida extracts may be safe for use in the management of diabetes mellitus and its associated biochemical complications.